Success story of acute abdomen in pregnancy-torsion ovary - Saidhandapani, Kalyani; Sadhana Karthikeyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Torsion ovary is one of the acute emergencies in pregnancy with prevalence of 2.7-3% with high maternal and fetal mortality rates. Delay in diagnosis leads to hemorrhage, infarction and necrosis resulting in loss of ovary or fetal loss. Although 26% adnexal torsion can occur in apparently healthy adnexa, exact etiology remains unknown, predisposing factors include larger cyst size, free mobility and long pedicle. Acute onset of pelvic pain followed by nausea and vomiting is the most common presenting symptom. High levels of clinical suspicion along with ultrasound and doppler aids in diagnosis. We present a case of 18 weeks multipara with acute abdomen diagnosed as ovarian torsion, emergency laparotomy was done and salphingo-oophorectomy was proceeded without disturbing gravid uterus. Pregnancy continued and an alive term baby delivered by normal vaginal delivery. Once torsion ovary is suspected, surgical management remains the treatment of choice.